Faktor-Faktor yang Berhubungan Minat Ibu dalam Pemilihan Alat Kontrasepsi Iud pada Wanita Usia Subur di Desa Cimanggu Kecamatan Cibeber Kabupaten Cianjur - Papat Patimah; Lenina Nurani (Universitas Malahayati Lampung, 2022)
ABSTRACT The government's policy on family planning currently leads to the use of long-term contraceptive methods. Intra Uterine Device (IUD) is one of the most effective and safe long-term contraceptives compared to other contraceptive methods such as the pill. The IUD contraception is very effective in reducing maternal mortality and controlling population growth rates because the effectiveness rate of use is up to 99.4% and the IUD can be used for a period of 3-5 years (hormonal type) and 5-10 years (copper type). The IUD contraceptive device is inserted into the uterus in various forms, consisting of plastic This study aims to determine the factors related to maternal interest in the selection of IUD contraceptives for fertile women in Cimanggu Village, Cibeber District, Cianjur Regency. This study used a quantitative approach with a cross sectional research design that was carried out in Cimanggu Village, Cibeber District, Cianjur Regency in September 2021–February 2022. The population was all women of childbearing age using a simple random sampling technique based on the formula for the estimation of the proportion of one population. Collecting data using a questionnaire distributed to respondents. Data analysis was univariate (frequency distribution) and bivariate (chi square). Results: The results of the analysis of the relationship with the mother's interest in the choice of IUD contraception showed that the significance level of P-value from a (0.05) means that there is no relationship between UISA and the choice of IUD contraception. children got P-value = 0.154, knowledge obtained P-value of 0.000, attitude obtained P-value = 0.000, contraceptive devices obtained P-value of 0.025, availability of officers obtained P-value of 0.082. The results of the analysis of the relationship with the mother's interest in the choice of IUD contraception showed that at a significance level of P-value from a (0.05), it means that there is no relationship between UISA and the choice of IUD contraception. P-value = 0.154, knowledge obtained P-value of 0.000, attitude obtained P-value = 0.000, contraceptive devices obtained P-value of 0.025, availability of officers obtained P-value of 0.082. Shows that respondents use non-IUD contraception more than respondents who use IUD contraception, most respondents have low education, and many respondents have children, from the reinforcing factor, namely husband's support, most of them do not support the use of IUD contraception. and pills. a small number of respondents stated that there were not enough tools and officers. The results of bivariate data analysis showed that the variables that were statistically related to the choice of IUD contraception were Knowledge, Attitude, completeness of contraceptive devices and husband's support. Keywords : IUD Contraception, Interest, Fertile Age ABSTRAK Kebijakan pemerintah tentang KB saat ini mengarah pada pemakaian metode kontrasepsi jangka panjang. Intra Uterine Device (IUD) adalah salah satu alat kontrasepsi jangka panjang yang paling efektif dan aman dibandingkan alat kontrasepsi lainnya seperti pil. Alat kontrasepsi IUD sangat efektif untuk menekan angka kematian ibu dan mengendalikan laju pertumbuhan penduduk karena tingkat efektifitas penggunaan sampai 99,4% dan IUD dapat digunakan untuk jangka waktu 3-5 tahun (jenis hormon) dan 5-10 tahun (jenis tembaga). Alat kontasepsi IUD dimasukkan kedalam rahim yang bentuknya bermacam-macam, terdiri dari plastic untuk mengetahui faktor-faktor yang berhubungan minat Ibu dalam pemilihan alat kontrasespi IUD pada wanita subur di Desa Cimanggu kecamatan Cibeber Kabuapaten Cianjur Penelitian ini menggunakan pendekatan kuantitatif dengan desain penelitian cross sectional telah dilakukan di Desa Cimanggu Kecamatan Cibeber Kabupaten Cianjur bulan September 2021–pebruari 2022. Populasi seluruh wanita usia subur dengan Teknik simple random sampling berdasarkan rumus estimasi proporsi satu populasi. Pengambilan data dengan menggunakan kuesioner yang dibagikan ke pada responden. Analisa data secara univariat (distribusi frekuensi) dan bivariat (chi square). Hasil analisis hubungan dengan minat ibu dalam pemilihan alat kontrasepsi IUD menunjukkan pada taraf signifikansi P-value dari a (0,05) berarti tidak ada hubungan anatara Uisa dengan pemilihan kontrasepsi IUD, Hasil uji statistik variable pendidikan diperoleh Pvalue = 0,889, jumlah anak didapatkan Pvalue = 0,154, pengetahuan diperoleh nilai Pvalue sebesar 0,000, sikap diperoleh Pvalue = 0,000, alat kontrasepsi diperoleh nilai Pvalue sebesar 0,025, ketersediaan petugas diperoleh Pvalue sebesar 0,082. menunjukkan bahwa Responden menggunakan kontrasepsi non IUD lebih banyak daripada responden yang menggunakan kontrasepsi IUD, sebagian besar responden berpendidikan rendah, dan responden banyak mempunyai anak, dari faktor penguat yaitu dukungan suami, lebih banyak tidak mendukung penggunaan kontrasepsi IUD tetap responden menjadi akseptor KB diantara nya suntik dan pil. sebagian kecil responden menyatakan kurang tersedia alat dan petugas. Hasil analisis data bivariat menunjukkan variable yang secara statistik berhubungan dengan pemilihan kontrasepsi IUD adalah Pengetahuan, Sikap, kelengkapan alat kontrasepsi dan dukungan suami. Kata Kunci: Usia Subur, Minat, Kontrasepsi IUD